The Kalam Khabari As a Prophetic Pedagogical Tool: Rhetorical Dimensions And Pragmatic Implications In Arba'in Nawawi - rasyadanfaiqal muhammadrasyadanfaiqal; shofiamajidakhoirulmuna; maghfirohizanimaulania; azzahrasyafikah (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study explores the rhetorical dimensions and pragmatic implications of kalam khabari (declarative speech) within prophetic discourse, specifically focusing on the Arba'in al-Nawawi compilation. While classical rhetoric often categorizes kalam khabari as merely an informative structure, this research addresses a theoretical gap by investigating its functional shift into a directive and normative pedagogical tool. Utilizing a qualitative descriptive-analytical method based on library research, this study applies the framework of the science of ma'ani to analyze purposively sampled hadiths. The findings reveal that the Prophet Muhammad (PBUH) systematically employed various forms of declarative sentences ibtida'i, talabi, and inkari not solely to convey factual realities, but as strategic performative instruments. These rhetorical structures function to establish absolute theological truths (At-Taqrir), deliver profound psychological admonitions (Tahdzir), and mandate binding legal regulations (Al-Amr al-Ilzami). By framing moral commands and warnings within logical facts, this indirect pedagogical method effectively minimizes psychological reactance, allowing Islamic morality and Sharia to be internalized willingly without appearing coercive. Ultimately, this research affirms that integrating classical Arabic rhetoric with modern pragmatics is crucial for uncovering the transformative educational guidance embedded within the Prophet’s sayings